THE EFFECT OF FOLKTALE BASED STORYTELLING METHOD ON STUDENTS’ SPEAKING ABILITY IN INSTITUT PENDIDIKAN TAPANULI SELATAN (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
The purpose of this research is to investigate whether there is a significant effect of using folktale based stotytelling method on students’ speaking ability at the second semester students of English Language Education Program in Institut Pendidikan Tapanuli Selatan. The research methodology is quantitative method. The sample was taken by using total sampling technique. The instrument of the reseacrh is speaking test. The data were then analyzed by using descriptive and inferential analysis, it was t-test formula by Arikunto. The results of the research are the mean score of students’ speaking ability before using folktale based stotytelling method is 51.5, it is categorized less, then after using using folktale based stotytelling method is 72.37, it is categorized good. The hypothesis testing showed that t-test was higher than t-table (17>2.04), it means that the hypothesis is accepted. The finding of research reveals that there is a significant effect of using folktale based storytelling method on students’ speaking ability at the English Language Education Program in Institut Pendidikan Tapanuli Selatan.